Tobacco (Nicotiana tabacum) PSY peptides and their potential roles in seed germination, vegetative growth, and leaf senescence under osmotic stress - Deng, Zhichao; Pan, Xiaolu; Wu, Rongrong; Yang, Yalun; Liu, Tao; Li, Wei; Zhang, Zenglin; Guo, Yongfeng (Frontiers in Plant Science, 2025)
IntroductionMembers of the Plant Peptides Containing Sulfated Tyrosine (PSY) family play critical roles in plant development and stress responses. While extensively studied in Arabidopsis, rice, and wheat, the biological functions of PSY peptides in tobacco (Nicotiana tabacum) remain poorly characterized. This study aims to identify NtPSY genes in tobacco and elucidate their roles in growth regulation and osmotic stress adaptation.MethodsA comprehensive bioinformatics approach was employed to identify NtPSY genes using tobacco genomic data and homology with Arabidopsis PSY sequences. Expression profiles under drought, salinity, and temperature stress were analyzed via qRT-PCR. Functional validation included virus-induced gene silencing (VIGS) of homologous genes in Nicotiana benthamiana and exogenous application of synthetic NtPSY1/NtPSY3 peptides to assess their effects on seed germination, seedling growth, and osmotic stress tolerance.ResultsA total of nine NtPSY genes were identified, the expression changes of which under different abiotic stresses were analyzed using qRT-PCR. The results showed that all NtPSY genes responded significantly to drought, salinity, and extreme temperature stress conditions. NtPSY1 and NtPSY3 were further analyzed for their function in development and response to osmotic stress. The results indicated that treatments of tobacco detached leaves and seeds with synthetic peptides can promote seed germination and seedling growth, while reducing tobacco’s tolerance to osmotic stress.DiscussionThe dual role of NtPSY peptides—promoting growth under optimal conditions while impairing stress tolerance—highlights their function as signaling molecules balancing growth-stress trade-offs. This mechanism aligns with PSY receptor-mediated pathways reported in Arabidopsis, where ligand binding inhibits stress signaling. The study provides novel insights into PSY peptide dynamics in tobacco and suggests potential applications for optimizing stress resilience in crops.